2015
DOI: 10.1074/jbc.m114.608497
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Mutant Isocitrate Dehydrogenase 1 (IDH1) via Disruption of a Metal Binding Network by an Allosteric Small Molecule

Abstract: Background: Mutant-selective IDH1 inhibitors are potential cancer therapeutics, but the mechanistic basis for their selectivity is not yet well understood. Results: Inhibitor binding modes and kinetic mechanisms were characterized. Conclusion:The inhibitors selectively inhibit mutant IDH1 by interacting with a magnesium-binding residue. Significance: Targeting metal-binding residues with drug-like small molecules is a feasible strategy for IDH1 inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
139
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(148 citation statements)
references
References 36 publications
(53 reference statements)
7
139
2
Order By: Relevance
“…Inhibitors of IDH1 MT and IDH2 MT were recently developed (23)(24)(25)(26)(27). Clinical trials of the IDH1 R132H inhibitor AGI-5198 (ClinicalTrials.gov NCT02073994) are in progress in solid tumors.…”
Section: Idh1mentioning
confidence: 99%
“…Inhibitors of IDH1 MT and IDH2 MT were recently developed (23)(24)(25)(26)(27). Clinical trials of the IDH1 R132H inhibitor AGI-5198 (ClinicalTrials.gov NCT02073994) are in progress in solid tumors.…”
Section: Idh1mentioning
confidence: 99%
“…According to these findings, it was suggested that differences in Mg 2+ binding between WT and mutant enzymes may contribute to the selectivity of inhibitors. 100 In the other study, the crystallographic analysis of the structure of another inhibitor (GSK321) bound to mutant IDH1 showed that the inhibitor binds to an allosteric site and freezes the enzyme into an open, catalytically inactive conformation. 100 At variance with the other inhibitor, two molecules of the inhibitor GSK 321 bind per enzyme dimer, and this binding was shown to be competitive with α-KG.…”
Section: Idh Inhibitorsmentioning
confidence: 98%
“…100 In the other study, the crystallographic analysis of the structure of another inhibitor (GSK321) bound to mutant IDH1 showed that the inhibitor binds to an allosteric site and freezes the enzyme into an open, catalytically inactive conformation. 100 At variance with the other inhibitor, two molecules of the inhibitor GSK 321 bind per enzyme dimer, and this binding was shown to be competitive with α-KG. 101 The biologic effect of this inhibitor on primary IDH1-mutant AML blasts was also tested, and showed an initial increase in viable cells, followed by a late reduction in cell viability coupled with an increase in apoptosis, as well as progressive induction of granulocytic differentiation of leukemic cells, as shown by cell morphology and membrane antigen expression.…”
Section: Idh Inhibitorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Separate discovery efforts around mutant IDH1 led by Sanofi (Cambridge, MA) (Deng et al, 2015) and GlaxoSmithKline (Collegeville, PA) (Okoye-Okafor et al, 2015) used a similar biochemical screen, although they prepared wild-type-IDH1/ mutant-IDH1 heterodimer protein (physiologic state) using the two most common IDH1 mutations (R132C and R132H) for their screening campaigns. In each case, they pursued distinct chemical scaffolds, and the primary in-cell confirmation of activity was demonstrated through inhibition of 2-HG production.…”
Section: A Case Study 1: Mutant Isocitrate Dehydrogenases 1 Andmentioning
confidence: 99%